IRISH OVERDETERMINATION: STRATEGIES FOR ENTERING AND LEAVING THE GAELTACHT - Ó GIOLLÁIN, Diarmuid (Studia Universitatis Babeș-Bolyai Philologia, 2018)
Irish Overdetermination: Strategies for Entering and Leaving the Gaeltacht. Irish and Gaels are terms that refer to historical and contemporary peoples. Both terms, however, are overdetermined, freighted both with negative stereotypes and impossible standards of cultural authenticity, such that the Irish and the Gaelic part in historical processes is distorted. This article looks at a difficult history in which Gaelic Ireland was nearly destroyed, yet from the eighteenth century, Gaelic heritage was accumulated in the capital, later providing fodder for a linguistic and cultural revival movement that reshaped modern Ireland. Marginal and yet central to modern Irish identity, the Gaelic inheritance today is threatened and thriving, and the Irish language is a minority language that has a superior constitutional standing to majority English. Rezumat. Supra-determinare irlandeză: strategii pentru intrarea și ieșirea din Gaeltacht. Irlandezi și Gaels sunt termeni care se referă la popoare istorice și contemporane. Ambii termeni, însă, sunt supra-determinați, încărcați atât de stereotipii negative cât și de standarde imposibile de autenticitate culturală, astfel încât partea irlandeză și cea gaelică în procesele istorice suferă distorsiuni. Articolul de față discută o istorie dificilă în care Irlanda gaelică a fost aproape distrusă, și totuși, începând din secolul XVIII, moștenirea gaelică s-a acumulat ca un capital, furnizând mai târziu materie primă pentru o micare de renaștere lingvistică și culturală care a modelat Irlanda modernă. Marginală și totuși centrală în identitatea modernă irlandeză, moștenirea gaelică astăzi e pe atât de amenințată pe cât de înfloritoare, iar limba irlandeză e o limbă minoritară care se bucură de un statut constituțional superior englezei majoritate. Cuvinte cheie: Irlandez, gaelic, identitate, rasism, autenticitate, limbaj, migrațiune.